Evaluating the Safety of Sodium Hypochlorite Usage as an Irrigation Solution in Acute Osteomyelitis: an Experimental Study in Rat Tibia via a Renewed Osteomyelitis Model - AKDENİZ, ESRA (My University, 2020)
Objective: The ideal irrigation solution for osteomyelitis surgery has not yet been clarified. The aim of this study is to evaluate the therapeuticeffect and the optimum concentration of sodium hypochlorite (NaOCl) solution for the mechanical treatment of acute osteomyelitis.Methods: Fourty tibias of 20 male Wistar rats were used. The medullas were percutaneously inoculated with Staphylococcus aureus ATCC25923 to induce acute osteomyelitis in tibias. One week later, rats were randomly assigned to 3 treatment groups and irrigated with 0.5%,1% and 5% NaOCl. Irrigation with saline was used at positive control group and any treatment was not given to negative control group. Allrats were sacrificed 24 hours after NaOCl irrigation. The degree of bacterial density, necrosis, inflammation and edema were evaluatedhistologically as; none (0), mild (1), moderate (2) and severe (3). Kruskal-Wallis and Dunn tests were used for statistical evaluations.Results: Acute osteomyelitis developed in all tibias. NaOCl treatment no matter the concentration reduced the bacterial density compared tonegative control group. The decrease in bacterial density and inflammation was significant at 0.5% NaOCl group compared to positive group(respectively; p=0.019, p=0.045), while the pairwise comparisons were statistically insignificant in terms of necrosis and edema. There wasnot any statistically difference between positive and 1%-5% NaOCl groups in terms of bacterial density.Conclusion: In conclusion, irrigation with 0.5% NaOCl was more therapeutic than saline, 1% NaOCl and 5% NaOCl concentrations for acutetibia osteomyelitis at rats while 0.5% NaOCl group was same with saline group in terms of safety to tissue.